A hybrid scheme using packet marking and logging for IP traceback. (12th April 2010) - Malliga, S.; Tamilarasi, A.
IP traceback is a mechanism for tracing IP packets back to their sources. Tracing mechanisms include packet marking and logging. Log based traceback has the ability to backtrack a single packet by logging each packet at intermediate nodes in the networks. Marking based traceback helps to embed the path information of the intermediate nodes in the packets and the embedded information is used by a victim to reconstruct the attack path. Recent researches show that the performance of hybrid methods comprising logging and marking are appreciable as they help to traceback a single attack packet with less storage overhead on routers. In this study, we use a hybrid approach based on marking and logging to traceback single attack packet with less storage and traceback overhead on routers. We show this through a mathematical analysis. We also evaluate the traceback accuracy of our system and other hybrid approaches. Additionally, the simulation results are also presented to verify the effectiveness of the proposed system.